EFEKTIVITAS PELAKSANAAN TUGAS DAN FUNGSI BHABINKAMTIBMAS DI DESA BULU TELLUE KECAMATAN TONDONG TALLASA KABUPATEN PANGKEP - KADIR, ABD.; Nurmiati, Nurmiati (Patria Artha University, 2023)
This research aims to determine the level of effectiveness, determine the supporting and inhibiting factors and the efforts made to increase the effectiveness of implementing the duties and functions of Bhabinkamtibmas in Bulu Tellue Village, Tondong Tallasa District, Pangkep Regency. The population in this study was the people of Bulu Tellue Village, Tondong Tallasa District, Pangkep Regency, consisting of the village head, all village officials, the RK head, the RT head, and 35 community leaders. In this research, a total sampling technique was used so that the number of samples was the same as the population. The data analysis used in this research is quantitative descriptive analysis. The results of the research show that: 1) The effectiveness of implementing the duties and functions of Bhabinkamtibmas in Bulu Tellue Village, Tondong Tallasa District, Pangkep Regency is on average 2.80 or is in the effective category; 2) Factors that support the implementation of the duties and functions of Bhabinkamtibmas in Bulu TellueVillage, Tondong Tallasa District, Pangkep Regency consist of: a) Bhabinkamtibmas controls the area of its duties; 2) Availability of supporting facilities and facilities; 3) Community support, while the factors that hinder the implementation of the duties and functions of Bhabinkamtibmas in Bulu Tellue Village, Tondong Tallasa District, Pangkep Regency